City of the plague god - Chadda, Sarwat (Disney-Hyperion, 2021)
"Thirteen-year-old Sikander Aziz has to team up with the hero Gilgamesh in order to stop Nergal, the ancient god of plagues, from wiping out the population of Manhattan in this adventure based on Mesopotamian mythology"--